Synergistic Antimicrobial Activity of Supplemented Medical-Grade Honey against Pseudomonas aeruginosa Biofilm Formation and Eradication - Carlos C. F. Pleeging; Tom Coenye; Dimitris Mossialos; Hilde de Rooster; Daniela Chrysostomou; Frank A. D. T. G. Wagener; Niels A. J. Cremers (MDPI AG, 2020)
Biofilms hinder wound healing. Medical-grade honey (MGH) is a promising therapy because of its broad-spectrum antimicrobial activity and the lack of risk for resistance. This study investigated the inhibitory and eradicative activity against multidrug-resistant Pseudomonas aeruginosa biofilms by different established MGH-based wound care formulations. Six different natural wound care products (Medihoney, Revamil, Mebo, Melladerm, L-Mesitran Ointment, and L-Mesitran Soft) were tested in vitro. Most of them contain MGH only, whereas some were supplemented. L-Mesitran Soft demonstrated the most potent antimicrobial activity (6.08-log inhibition and 3.18-log eradication). Other formulations ranged between 0.89-log and 4.80-log inhibition and 0.65-log and 1.66-log eradication. Therefore, the contribution of different ingredients of L-Mesitran Soft was investigated in more detail. The activity of the same batch of raw MGH (1.38-log inhibition and 2.35-log eradication), vitamins C and E (0.95-log inhibition and 0.94-log eradication), and all ingredients except MGH (1.69-log inhibition and 0.75-log eradication) clearly support a synergistic activity of components within the L-Mesitran Soft formulation. Several presented clinical cases illustrate its clinical antimicrobial efficacy against Pseudomonas aeruginosa biofilms. In conclusion, MGH is a potent treatment for Pseudomonas biofilms. L-Mesitran Soft has the strongest antimicrobial activity, which is likely due to the synergistic activity mediated by its supplements.